Tolerance Discourse In Interfaith Dialogue In Habib Husein Ja - Soraya, Soraya; Mualimin, Mualimin (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2022)
The purpose of this research was to know the tolerance discourse in interfaith dialogue in Habib Husein Ja